MIQUÉIAS 6,1-8: UM TEXTO PARADIGMÁTICO NA INTERFACE DA CRÍTICA PROFÉTICA COM A SABEDORIA ISRAELITA - Suaiden, Silvana (2012)
This master dissertation in Literature and Religion in the Biblical World has the objective of making a exegetical and hermeneutical comment of a text which has been recognized as a prophetic one, and its relationship to the theological, anthropological and literary with the Israeli sapiential universe in post-exilic period. It is about the study of Micah 6,1-8, whose focus of investigation has developed from the discourse analysis and the hypothetical confluence of literary genres, namely, the prophetic and sapiential. Considered under formal aspects, contextual and of theological anthropology content, the studied text is the result of the composition of several literary genres and manifests, internally conflicting theologies ranging from the interpretation of the history of Israel to the religious practice with their conceptions of God. Micah 6,1-8, played here from modern exegetical methodologies and contextual and anthropological approaches configured as a true synthesis of non-hegemonic deuteronomist interpretation of events of Exodus and the message of biblical prophets of the eighth century BC Micah, Amos, Hosea and Isaiah. We are before a text that presents itself at the same time, cohesive and carrying different universes and voices in his composition. His discourse, whose content born of the conflict between projects and groups in the post-exilic period, redeems old memories of an exodus that goes through marginal subjects and reinterprets the prophetic critique in his role as an ethical and theological insight, however, in the sapiential format. For the socio theological depth and by the no sacrificial proposal of his discourse, Micah 6,1-8 has been a continually revisited text inside the Theology of Liberation in Latin America, inspiring much of his production.